Synthesis of Substituted Indole-3-carboxylates by Iron(II)-Catalyzed Domino Isomerization of 3-Alkyl/aryl-4-aryl-5-methoxyisoxazoles - Bodunov, Vladimir A.; Galenko, Ekaterina E.; Galenko, Alexey V.; Novikov, Mikhail S.; Khlebnikov, Alexander F. (Synthesis, 2018)
The iron(II)-catalyzed domino isomerization of 3-alkyl/aryl-4-arylisoxazoles provides a selective access to a wide range of structurally diverse highly substituted indole-3-carboxylates. The operational simplicity, high atom efficiency, and the use of stable starting materials and an inexpensive and low-toxicity catalyst are some of the attractive features of this tandem double ring-opening–ring-closure strategy.
Keywords: indoles; isoxazoles; isomerization; domino reactions; iron(II) chloride catalysis